Direct access to 2-aryl substituted pyrrolinium salts for carbon centre based radicals without pyrrolidine-2-ylidene alias cyclic(alkyl)(amino)carbene (CAAC) as a precursor12. Issue 14 (13th March 2019) - Mandal, Debdeep; Sobottka, Sebastian; Dolai, Ramapada; Maiti, Avijit; Dhara, Debabrata; Kalita, Pankaj; Narayanan, Ramakirushnan Suriya; Chandrasekhar, Vadapalli; Sarkar, Biprajit; Jana, Anukul
Abstract : A new strategy to synthesise 2-substituted pyrrolinium salts. Abstract : The synthesis of organic radicals is challenging due to their inherent instability. In recent years, cyclic(alkyl)(amino)carbene (CAAC)-derived 2-substituted pyrrolinium salts have been used as synthons for the synthesis of isolable carbon-based radicals. Herein, we report a direct, easy and convenient method for the synthesis of 2-aryl substituted pyrrolinium salts without using CAAC as a precursor. These cations can be reduced to the corresponding radicals. The influence of the aryl substituent at the C-2 position on radical stabilization and dimerization has been investigated. Because of the large scope of our strategy (capability to modulate different substituents at all the C - and N -centres of the pyrrolinium salts), it has the merit to be an extremely effective and productive route for generating carbon-based radicals whose stability as well as reactivity can be varied.